Re-Os age of molybdenite from the Hannivka deposit, Kryvyi Rih structure, Ukrainian Shield - Yu. Ye. Khomych; V. V. Sukach; L. V. Shumlyanskyy; S. M. Bondarenko; V. O. Syomka; S. Tessalina; M. M. Reshetnyk (Мінеральні ресурси України)
This article presents the results of isotopic dating of molybdenite using the Re–Os method to determine the age of mineralization at the Hannivka deposit. Analytical studies were carried out at the John de Laeter Centre (JdLC) at Curtin University, Western Australia. Three molybdenite samples from the Hannivka deposit (1/380.6, 6/358.0, 1/368.8) were dated. The concentration of Re in these samples is relatively consistent: 20–32 ppm. The content of radiogenic osmium-187 shows slight variability. The model age for the Hannivka molybdenite samples shows a significant range from approximately 1.85 to 2.3 Ga. Individual model ages were determined as 1852 ± 30 Ma for sample 1/380.6; 2097 ± 9 Ma for sample 1/368.8; 2316 ± 11 Ma for sample 6/358.0. This age range corresponds to Paleoproterozoic. The mean model age based on these three samples is 2.088 Ga. For comparison, two samples from the Serhiivka Au-Mo deposit were also analyzed (3219/189.5 and 3217). These samples had significantly higher Re and Os concentrations (3–6 times higher) compared to the Hannivka samples. The model age for sample 3219/189.5 from Serhiivka is 3013 ± 17 Ma, which is in good agreement with previously obtained data 3.0–3.1 Ga for the Serhiivka mineralization using Re–Os method. This age corresponds to the Mesoarchean. The model age for sample 3217 is 1811 ± 39 Ma, which is significantly younger and might indicate weak pulses of Paleoproterozoic ore formation at Serhiivka, similar to the major events at Hannivka. The model ages obtained for Hannivka suggest a genetic link to Paleoproterozoic tectono-magmatic events. These events were active in the Inhul megablock and expressed themselves in the Kryvyi Rih-Kremenchuk suture zone and Kryvyi Rih structure through the intrusion of veins and lenses of Kropyvnytskyi granitoid complex (dated at 1959 ± 36 Ma) and aplite-pegmatoid granites (dated at 1.8 Ga).